Digital literacy to improve the professionalism of online media journalists in Bengkulu, Indonesia - Gushevinalti,; Suparman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to know the competence of digital literacy Online media journalists in Bengkulu City in complying with cyber media guidelines to support professionalism ranging from verification activities to writing news or delivering coverage to editors. Also to identify efforts made by online media journalists in Bengkulu City using tools for fact checking to verify news materials. This research uses a qualitative descriptive approach. The data collection method uses interviews, observation and focus group discussion. This study's Informants are journalists registered as members of the Indonesian Cyber Media Network (JMSI) and the Indonesian Cyber Media Union (SMSI) in Bengkulu. The results of the study concluded that the literacy of journalists in using digital media is quite good. However, it cannot be included in the excellent category because journalists lack knowledge and skills in digital literacy competencies. Moreover, journalists knowledge and skills upgrades such as fact-checking or digital literacy training is minimal, eventhough journalists understand the challenges in publishing journalistic works today. Generally, journalists use tools for checking facts or verifying sources of information either conventionally or manually. However, the strength in publishing journalistic works is the collaboration of cyber media within press companies to produce quality work. The FGD found that only Bengkulu Eskpress conducts fact checks in its journalistic work, because its journalists have received fact-check training conducted by the Alliance of Independent Journalists (AJI). The study results also show that online media utilize digital-based tools because they have received fact checking training, namely Bengkulu Ekspress.